A study on the association between job-related motivational factors and job satisfaction. Job satisfaction among rank-and-file officers of the Royal Customs Department. A case study at Port Klang Selangor, Malaysia / Nur Ainisa Arifin - Arifin, Nur Ainisa (Faculty of Administrative Science and Policy Studies, 2003)
Motivation and satisfaction may determine the successful and failure of an organization. Meaning that organization can sustain their performance when they have dedicated, competitive workforce and quality of motivation factors then will lead to job satisfaction as well. Therefore, these studies are examines the factors that contribute to motivation as well as job satisfaction. This study is conducted at Royal Custom Department in Port Klang, Selangor. A sample of 60 staffs was interviewed and self-administered questionnaire. The study tries to find the relationship between demographic factors (gender, age, status, tenure, education, monthly income and race) with job satisfaction and motivational factors, the relationship between extrinsic motivational factors (good wages, good working condition, tactful discipline and job security) and intrinsic motivational factors (full appreciation of work done, sympathetic help with personal problem, opportunity for career growth, interesting and challenging work, feeling of being involved in organization, and company loyalty to employees) with job satisfaction. The method that have been used in this study in order to analyze the data collected are Statistical Package for Social Science (SPSS). The finding is hopefully can contribute and help the Custom Department in order to upgrade and increase their motivational factors which then determine the employees' job satisfaction.